Perceptions About the Labor Market Integration of Refugees: Evidences from Syrian Refugees in Jordan - Zeynep Sahin Mencutek; Ayat J. Nashwan (Journal of International Migration and Integration, 2020)
This article focuses on the refugees' labor market integration in the immediate host countries. Drawing from the experience of Syrian refugees in Jordan, it describes how the integration in labor market depends on the alignment of four perspectives: (1) host state perspective, materialized through legal regulations about refugee employment; (2) refugee perspective that refers to refugees' access to labor market and challenges they face; (3) host community perspective that implies to the recognition, approval, or reactions of host communities to the refugee employment; and (4) donor perspective that appears with the intervention of international actors through development aid or general support to refugees' working rights. To explore these diverging perspectives and their implications about the labor market integration of Syrian refugees in Jordan, the data is gathered from ethnographic policy analysis and stakeholder interviews in urban areas and camps. We argue that the refugees' legal right to work is one of the most contentious policy issues not only for Jordanian state but also for its relations with Jordanian citizens, refugees, and donors. From the perspective of donors, ensuring Syrians' legal access to labor market in the immediate host countries, like Jordan, is a policy tool for keeping refugees in the origin region. At the host community level, the issue appears as a source of dilemma; because refugee employment is a critical domain for refugees' self-reliance and local integration on the one hand, it is perceived as the source of competition for already scarce job opportunities on the other hand. For refugees themselves, an access to labor market and getting support are ways of gaining sustainable livelihood opportunities, self-reliance, and dignity. However, this access is marked by severe conditions of exploitation, vulnerability, and discrimination in working places as well as the anti-refugee rhetoric of local host communities. Programming in refugee employment necessitates taking all these four perspectives into account.
Keywords: 300; Refugee policies; Labor market integration; Syrian refugees; Jordan; Refugee employment; Compact